Scientific Analysis Of Monuments Included In The List Of Cultural Heritage Of The Islamic World In Bukhara - Sultonov I.Z; Maxmatqulov I.T (Genius Journals, 2023)
The article contains information about a number of historical monuments located in the city of Bukhara and their inclusion in the list of cultural heritage of the Islamic world, their history, architecture. At the same time, detailed opinions are presented about the state of repair of historical monuments and the preservation of their material value.
Keywords: Historical monument; complex; Khurasan